2014
DOI: 10.1164/rccm.201312-2181oc
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime Cross-Coverage Is Associated with Decreased Intensive Care Unit Mortality. A Single-Center Study

Abstract: In this single-center study exposure to cross-covering fellows was associated with a decrease in ICU mortality and with more nighttime decisions. Our findings contradict the dominant hypothesis that cross-coverage is associated with worse outcomes, and suggest that a "second look" by cross-covering fellows may mitigate cognitive errors. Future interventions to improve patient safety in ICUs should focus both on the quality of handoffs and on strategies to decrease cognitive errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 30 publications
1
36
0
Order By: Relevance
“…Two large multicentre observational studies involving 49 and 143 ICUs have previously demonstrated no benefits of night-time intensivists, regardless of daytime staffing model [54,55]. Others studies showed however an improved ICU mortality with night-time physician staffing [38,56]. …”
Section: Discussionmentioning
confidence: 99%
“…Two large multicentre observational studies involving 49 and 143 ICUs have previously demonstrated no benefits of night-time intensivists, regardless of daytime staffing model [54,55]. Others studies showed however an improved ICU mortality with night-time physician staffing [38,56]. …”
Section: Discussionmentioning
confidence: 99%
“…A potential mechanism for the latter effect is communication of an “authoritative” summary of each patient’s clinical status that is insufficiently challenged by the on-call team when patients deteriorate. This hypothesis is supported by a single-center study that found more nighttime decisions and lower ICU mortality in patients exposed to on-call cross-covering fellows [19]. These findings contradict the dominant hypothesis that cross-coverage is associated with worse outcomes, and suggest that a “second look” by cross-covering fellows may mitigate cognitive errors.…”
Section: Discussionmentioning
confidence: 90%
“…(7) These can be errors of omission or corruption of information, (12) impact clinical decision making (13) and discharge planning. (7) …”
Section: Challenges To Handovers In Critically Ill Patientsmentioning
confidence: 99%
“…These data suggest that the incoming clinician's different perspective may have helped them identify the problems that were overlooked by the daytime clinicians. (13) Once we acknowledge this crucial function of re-thinking about the patient during handovers, it is clear that we need to focus not only on what information is communicated but also on the interactions between clinicians during a handover.…”
Section: Challenges To Handovers In Critically Ill Patientsmentioning
confidence: 99%